Analysis of the Application of the CHSE Program in 3 and 4 star hotels in Berastagi Tourism City - Andora Jusuf Ahmad (Politeknik Pariwisata Medan, 2021)
This study aims to find out how the understanding of hotel employees in Berastagi to the CHSE (Hygiene, Health, Safety, and Environmentally friendly) program applied by the government to hospitality businesses. This type of research is qualitative descriptive research. The results concluded that In general, employees of 3- and 4-star hotels in Berastagi city understand the CHSE program that the government applies to hospitality businesses. The implementation of health protocols in every 3 and 4 star hotels in Berastagi city with the provision of hand washing areas and hand sanitizer in the main area of the entrance and other public areas, application of body temperature checks on every guest who comes and the presence of a distance guard in the hotel's public facilities such as the lobby area. The influence felt on the occupancy rate of rooms in 3- and 4-star hotels in Berastagi city after the CHSE program was implemented by the government, especially felt during the Week end.